Naming of Men in the 16- 17th century of the Grand Dutchy of Lithuania in the Documents of the Army - Čirūnaitė, Jūratė (Respectus Philologicus, 2001)
In the whole Grand Duchy of Lithuania, except Volynė, patronymic male naming system is predominant. Patronymics in the whole GDL, except Žemaitija, have derivatives only of Slavic suffixes such as -ovič, -evič, -ič. Only in Žemaitija, aside Slavic suffixes, patronymics are formed out of Lithuanian patronymic suffixes. Not all names have one patronymic. Sometimes there are two of them. The first one should be considered as a name derived from the name of one’s father, the second one is a name of one’s father’s father. We can find data about the early surnames in the documents of 1567–1631.